To solve the equation \(-4 + xy = -2y\) when \(x = 0\), let's substitute \(x = 0\) into the equation.
-
Substituting \(x = 0\): \[ -4 + 0 \cdot y = -2y \] This simplifies to: \[ -4 = -2y \]
-
Solving for \(y\): To isolate \(y\), divide both sides by -2: \[ y = \frac{-4}{-2} = 2 \]
Thus, the solution for when \(x = 0\) is \(y = 2\).
However, you mentioned that you want \(y = 4x - 5\), \(y = 15\).
To check if that matches:
-
Using the equation \(y = 4x - 5\):
- When \(x = 0\): \[ y = 4(0) - 5 = -5 \]
-
Using \(y = 15\):
- This is a constant value independent of \(x\).
Summary of Solutions:
- When \(x = 0\), the solution you get from the original equation \(-4 + xy = -2y\) is \(y = 2\).
- The equations \(y = 4x - 5\) and \(y = 15\) give different results for \(y\) when \(x = 0\) (namely, -5 and 15 respectively).
Therefore, the requirement you mentioned to have \(y = 4x - 5\) or \(y = 15\) doesn't directly correspond with \(x = 0\) based on the initial equation.
If you need the equation to yield those specific values, additional context or modifications may be required. Please clarify if you need a different form of manipulation or constraints.